Protective Effects of Sacubitril/Valsartan on Cardiac Fibrosis and Function in Rats With Experimental Myocardial Infarction Involves Inhibition of Collagen Synthesis by Myocardial Fibroblasts Through Downregulating TGF-β1/Smads Pathway - Wu, Meifang; Guo, Yanguang; Wu, Ying; Xu, Kaizu; Lin, Liming (Frontiers in Pharmacology, 2021)
Objectives To investigate the effect and mechanism of sacubitril/valsartan on myocardial fibrosis in rats following experimental myocardial infarction and in TGF-β1-treated myocardial fibroblasts. Methods Male Sprague-Dawley (SD) rats were subjected to coronary artery ligation to establish myocardial infarction and intragastrically fed vehicle, valsartan (Val, 32 mg/kg, once-daily) or sacubitril/valsartan (Sac/Val, 68 mg/kg, once-daily) for 4 weeks. In parallel, myocardial fibroblasts (MFs) isolated from neonatal SD rats were exposed to hypoxia and treated with TGF-β1 (5 ng/mL) plus vehicle, Val (10-7-10-5 M) or Sac/Val (10-7-10-5 M). Rat cardiac function and fibrosis were measured by echocardiography and histological method, respectively. MFs viability and collagen synthesis were determined by cell counting kit-8 and enzyme-linked immunosorbent assay, respectively. Protein expressions of TGF-β1, Smad3, phosphorylated Smad3 (p-Smad3), and p-Smad3 subcellular localization were detected by immunoblotting and immunocytochemistry. Results Sac/Val significantly improved cardiac structure and function in rats after myocardial infarction, including decreased left ventricular end-diastolic diameter and interventricular septal thickness, increased ejection fraction, and reduced myocardial collagen volume fraction and type Ⅰ and type Ⅲ collagen levels, and this effect was superior to that of Val. Besides, Sac/Val inhibited myocardial TGF-β1 and p-Smad3 protein expression better than Val. Mechanically, Sac/Val significantly attenuated TGF-β1-induced proliferation and collagen synthesis of MFs, and inhibit Smad3 phosphorylation and nucleus translocation, and this effect outperformed Val. Overexpression and silencing of Smad3 enhanced and reversed the inhibitory effects of Sac/Val on TGF-β1-induced collagen synthesis by MFs, respectively. Conclusions Sacubitril/valsartan improves cardiac function and fibrosis in rats after experimental myocardial infarction, and this effect is related to the inhibition of collagen synthesis in myocardial fibroblasts by inhibiting the TGF/ Smads signaling pathway.